Effect of the angular offset of the stator windings on DSIM performance - Lounnas, Fatma; Haddad, Salah (Institute of Advanced Engineering and Science, 2025)
The study outlined in this paper aims to analyze the effect of the different displacement angles between the two stator windings on the performance of a dual stator induction motor, which is a squirrel cage induction motor with two identical windings in its stator. The rated power of each winding is 1.1 kW and fed by an inverter operating with the pulse width modulation technique. The analytical model of the machine is used to analyze its characteristics to investigate the impact of the displacement angles between the two stator windings. A simulation program for the system has been developed using MATLAB/Simulink. Simulation results characterizing the comportment of this machine for different displacement angles of the stator windings show that the torque pulsations are noticeably lower at 30° shift than in the other two scenarios of 0° and 60°, the model exhibits noteworthy performances at this shift. The torque pulsations are noticeably lower at 30° shift than in the other two scenarios of 0° and 60°, and the model exhibits noteworthy performance at this shift. In this case, there are also reduced rotor current ripples, which decrease rotor heating. Despite this, the harmonics increased the peak stator phase currents for a 30° electrical offset.